Representation of The Conflict Between KPK And POLRI In Susilo Bambang Yudhoyono’s Speech - Bobby Sander (Passage, 2016)
This paper is entitled “Representation of the Conflict between KPK and POLRI in Susilo Bambang Yudhoyono’s Speech”. By employing a sociocognitive approach in accordance with the categories of semantic macrostructure and microstructure proposed by van Dijk (2008), the study demonstrates how the representation of the conflict between KPK and POLRI is projected and the ideology behind the former President’s speech. This study focuses on the former President Susilo Bambang Yudhoyono’s speech on October 8th, 2012, which presents his standpoint towards the conflict. The analysis shows that the conflict between KPK and POLRI is represented as frailty of the state institutions in enforcing the law, therefore showing a great political crisis. Regarding the analysis of microstructure, this study also finds that the President shows his full support for KPK more than POLRI as he questions the accusation of Novel Baswedan and the DPR’s offer related to the readjustment of KPK’s regulation. Furthermore, the President shows his egocentric demeanour by significantly emphasising his attempt of reconciliation in response to the public’s expectation. Additionally, the president considers the conflict as a collective responsibility. This consideration is then viewed as a strategy to restore his blackened reputation due to the public’s consideration of the government’s inactivity in resolving the conflict and therefore reflexes a social democracy. Keywords: representation, sociocognitive approach, ideology, macrostructure, microstructure